Giant chondroma of the sternum mimicking a mediastinal mass. Issue 8 (August 1990) - Fink, Gershon; Bergman, Michael; Levy, Moris; Avidor, Irena; Spitzer, Shimon
Abstract : A 64 year old man with a giant benign sternal chondroma presented with cough as his sole complaint.